Fixed point theorems for prešić almost contraction mappings in orbitally complete metric spaces endowed with directed graphs - Pornpimon Boriwan (2018)
© 2016, North University of Baia Mare. All rights reserved. The main aim of this paper is to introduce a class of generalized contractions in product spaces in the sense of Prešić. Some examples and fixed point theorems for such introduced mappings in the setting of orbitally complete metric spaces are proved. The results presented here extend and include many existing several results in the literature.